Transformations des classes populaires et de l’offre scolaire à São Paulo - Graziela Serroni Perosa; Adriana Santiago Rosa Dantas; Helena de Souza Marcon; Isamara Lopes Rocha Cruz (Brésil(s), 2015)
In Brazil, the distribution of social classes between public and private schooling establishments is highly unequal, since private schools recruit most of their pupils from socially privileged families, whereas public schools mainly receive pupils from families of more modest means. In this context, how can we explain the recent appearance of private establishments in Ermelino Matarazzo, a low-income neighbourhood in the suburbs of São Paulo? In an attempt to respond to this question, we first explore the results of a statistical analysis, showing the relative position of different district councils (subprefeituras) in the city’s social space, then examine, by means of ethnographic interviews, some clues relating to diverse factors that may have contributed to the implementation of a process of social ascension based on scholarly excellence.